Analisis Capacity Building Pilot Dalam Manajemen Sumber Daya Manusia Pada PT Garuda Indonesia - Fahrul Anwar Syadat; Mohamad Irfanul Hakiem; Eka Rofiyanti (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to identify and analyze capacity building, obstacles in increasing capacity building and efforts/solutions to overcome these obstacles. This is based on the imbalance between the operation of the pilot training system and the needs of the pilot. There were 20% of pilot trainees who had their training postponed and of the 16 required trainings, around 30% of the pilots trained only attended 4 of the trainings. Total training does not include 13 Specialized Training. This research was conducted at PT Garuda Indonesia from April to August 2021. This study used a qualitative approach. Data was collected by observation, literature study, and interviews with 7 informants. The concept used in this research is capacity building. The results of this study are that the system for increasing capacity building is very good because Garuda Indonesia has its own training plan, but in practice there are currently obstacles due to the Covid-19 pandemic, where out of around 16 basic training, only 4 trainings are carried out. by prospective pilots and no specialized training has been followed. PT. Garuda Indonesia provides a forum for all its employees in the form of associations in each field, such as that of Garuda pilots, there is an association called the Garuda Pilots Association (APG) which accommodates various suggestions, inputs, complaints and various improvement efforts from all existing pilots to submitted to the leadership through the APG